Efficacy and predictive factors of immune checkpoint inhibitors in metastatic breast cancer: a systematic review and meta-analysis. (August 2020) - Zou, Yutian; Zou, Xuxiazi; Zheng, Shaoquan; Tang, Hailin; Zhang, Lijuan; Liu, Peng; Xie, Xiaoming
Background: Immune checkpoint inhibitors (ICIs) have shown encouraging treatment efficacy for metastatic breast cancer in several clinical trials. However, response only occurred in a small population. Evidence predicting response and survival of patients with metastatic breast cancer following ICI treatment with existing biomarkers has not been well summarized. This review aimed to summarize the efficacy and predictive factors of immune checkpoint therapy in metastatic breast cancer, which is critical for clinical practice. Methods: PubMed, Embase, Cochrane Library, Web of Science, www.clinicaltrials.gov, and meeting abstracts were comprehensively searched to identify clinical trials. The outcomes were objective response rate (ORR), treatment-related adverse events (trAEs), immune-related adverse events (irAEs), progression-free survival (PFS), and overall survival (OS). Results: In this review, 27 studies with 1746 patients were included for quantitative synthesis. The pooled ORR was 19% [95% confidence interval (CI) = 12–27%]. Programmed death-ligand 1 (PD-L1)-positive patients had a higher response rate [odds ratio (OR) = 1.44, p  = 0.01]. First-line immunotherapy had a better ORR than second-line immunotherapy (OR = 2.00, p  = 0.02). Tumor-infiltrating lymphocytes (TILs) ⩾5% (OR = 2.53, p  = 0.002) and high infiltrated CD8+ T-cell level (OR = 4.33, p  = 0.006) were ideal predictors of immune checkpoint therapy response. Liver metastasis indicated poor response (OR = 0.19, p  = 0.009). However, the difference was non-significant in ORR based on age, performance status score, lymph node metastasis, and lactate dehydrogenase (LDH) level. In addition, the PD-L1-positive subgroup had a better 1-year PFS (OR = 1.55, p  = 0.04) and 2-year OS (OR = 2.28, p  = 0.02) following ICI treatment. The pooled incidence during ICI therapy of grade 3–4 trAEs was 25% (95% CI = 16–34%), whereas for grade 3–4 irAEs it was 15% (95% CI = 11–19%). Conclusions: Metastatic breast cancer had modest response to ICI therapy. PD-L1-positive, first-line immunotherapy, non-liver metastasis, and high TIL and CD8+ T-cell infiltrating levels could predict better response to ICI treatment. Patients with PD-L1-positive tumor could gain more survival benefits from immune checkpoint therapy.